ANALISA FAKTOR-FAKTOR PERSONAL BRANDING TERHADAP KESIAPAN KERJA MAHASISWA STMIK SINAR NUSANTARA SURAKARTA - Wibowo, Ari; Rimawati, Elistya (JURNAL ILMIAH EDUNOMIKA, 2024)
The world of work considers that graduates with high competence are those who have technical skills, soft skills and good behavior. In addition to attaching importance to the aspect of ability to acquire and work together to compete in the labor market competition, the concept of personal branding is important as a tool to win the competition. A friendly and always confident character coupled with problem-solving skills has become a personal branding for a student to be ready to face competition in the world of work. In addition to personal branding in the real world, it turns out that personal branding in cyberspace is no less important as a digital footprint that continues to be recorded. The current aspect of social media is quite a consideration for new HR recruiters in every company. The collection of research data was carried out online through a google form using a structured questionnaire. A total of 52 research samples were recruited using the purposive sampling method. This study uses the SmartPLS statistical analysis tool to process data. The results of the study show that soft skills and social media from students have a significant positive effect on student work readiness. Meanwhile, daily behavior is considered to have no effect on students' work readiness. The value of R2 = 0.471 explains that around 47% of the variance of the student work readiness variable is caused by the soft skill variable and student social media in the model.